Bridging Diversity and Innovation: The Moderating Role of Cohesive and Hierarchical Organizational Culture - Hyunji Ju; Yeonbae Kim (SAGE Open)
This study explores the intricate relationship between workforce diversity and innovation in high-tech industries. We introduce a cohesive and hierarchical organizational culture (CHOC) as a key factor influencing this relationship. We propose that fostering a CHOC can enhance innovation through workforce diversity. Cohesiveness promotes collaboration and alignment of goals, while a hierarchical culture improves efficiency through structured processes. Together, they create an environment where diverse individuals can effectively collaborate, foster collective workforce capabilities, and ultimately drive innovation. Our findings suggest the importance of promote a CHOC to fully leverage the potential of their diverse workforce. It also provides insights for theoretical development and practical remedies for organizations looking to enhance innovation through diversity. However, limitations exist. Our data is from 216 high-tech firms and 2,906 employees in a specific context, limiting generalizability. Unexplored variables may influence the diversity-innovation relationship, offering future research opportunities.